Role of Convex Probe Endobronchial Ultrasound in the Diagnosis and Treatment of Nonmalignant Diseases - Aljohaney, Ahmed A. (Pulmonary Medicine, 2019)
Here we present a comprehensive review of the literature concerning the utility of convex probe endobronchial ultrasound (CP-EBUS) in the diagnosis and treatment of nonmalignant conditions and discuss the associated complications. CP-EBUS has been conventionally used for the staging of lung cancer and sampling of mediastinal and hilar nodes. However, its application is not limited to malignant conditions, and it is gaining acceptance as a diagnostic modality of choice for nonmalignant conditions such as tuberculosis, sarcoidosis, pulmonary embolism, thyroid lesions, and cysts. Moreover, its therapeutic value allows for extended applications such as mediastinal and thyroid cyst drainage, fiducial marker placement for radiation therapy, and transbronchial needle injection. The noninvasiveness, low complication rate, high diagnostic yield, and satisfactory sensitivity and specificity values are the main attributes that lend credence to the use of CP-EBUS as a standalone primary diagnostic and therapeutic tool in pulmonary medicine in the foreseeable future.